EXPLORATIVE IDEAS ABOUT THE COMMUNICATIVE IDENTITY OF THE TEACHER (PANGEEA, 2025)
Is there a communicative identity of the teacher? What communicative elements do we develop to succeed and establish an excellent didactic relationship with the students? I tried a few answers using a technique I called contextual communicational description. The exploratory study carried out confirms the fact that the communicative identity of the teacher is built and negotiated continuously in the relationship with the students.
Keywords: teacher; communicational identity; communicational description; student-teacher communication